Realisme Magis Menurut Wendy B. Fariz dalam Novel Sihir Mesir di Tanah Jawa Karya Kisah Tanah Jawa - Hasem Ashari; Achmad Wahidy; Masnunah Masnunah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
The belief in myths today remains deeply embedded in the lives of Indonesian people, as shown by mystical stories that continue to be accepted, retold, and believed within society. One indication that mystical matters still have cultural relevance can be found in the literary work of the novel Egyptian Magic in Java by the Tale of the Land of Java team. The novel narrates the influence of magic believed to have been brought from Egypt to the East Indies and presents mystical experiences within a recognizable social and historical setting. This research aims to reveal the level and form of magic represented in the novel by applying the concept of magical realism proposed by Wendy B. Faris. The study focuses on how magical elements are integrated into realistic narration without eliminating the cultural meanings attached to them. To obtain research data, this study uses library research techniques through careful reading, identification, and classification of relevant textual data. The results of this research are expected to describe findings related to the five dimensions of magical realism, namely the irreducible magical elements, the phenomenal world, unsettling doubts, merging realism, and the disruption of time, space, and identity in the novel.